2021
DOI: 10.1016/bs.abr.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Natural deep eutectic solvents as performance additives for biocatalysis

Abstract: Following ionic liquids, (natural) deep eutectic solvents ((NA)DES) are receiving significant attention as performance additives for biocatalytic reactions.(NA)DES are increasingly evaluated as solvents to replace water in hydrolase-catalysed esterification reactions thereby shifting the reaction equilibrium. They also frequently outperform water in terms of solubility properties of hydrophobic reagents and thereby enable higher space-time yields. Furthermore, (NA)DES frequently exceed stabilising effects on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 89 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…The choice of the solvent plays thereby a central role in developing future biocatalytic applications. In the past few years, deep eutectic solvents (DESs) have emerged as a new solvent class for biocatalysis and have been labeled as the ‘solvent of the 21st century’ . The DESs, as first described by Abbot et al, can be formed by mixing a quaternary ammonium salt (e.g., choline chloride (ChCl)), acting as a hydrogen bond acceptor (HBA), with a hydrogen bond donor (HBD, e.g., glycerol and urea).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the solvent plays thereby a central role in developing future biocatalytic applications. In the past few years, deep eutectic solvents (DESs) have emerged as a new solvent class for biocatalysis and have been labeled as the ‘solvent of the 21st century’ . The DESs, as first described by Abbot et al, can be formed by mixing a quaternary ammonium salt (e.g., choline chloride (ChCl)), acting as a hydrogen bond acceptor (HBA), with a hydrogen bond donor (HBD, e.g., glycerol and urea).…”
Section: Introductionmentioning
confidence: 99%
“…The use of deep eutectic solvents (DESs) and DES/buffer mixtures as a medium for biocatalytic reactions requires taking into account their effect on the activity and stability of enzymes. Choline chloride-based DESs are in most common use [ 29 , 34 , 35 , 36 , 37 ]. However, chloride ions inhibit the activity of fungal laccases [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, enzymatic reactions proceed under ‘mild’ operating conditions, namely at pH values close to neutral, room temperature, under atmospheric pressure and in the absence of toxic organic solvents and meet the requirements of sustainable chemistry [ 29 , 33 , 34 ]. The use of DESs and water (buffer)/DES mixtures as media for enzymatic reactions is currently reported for a limited range of biocatalysts [ 29 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biocatalytic reactions might be inhibited by the low mass-transfer efficiency and the toxicity of hydrophobic substrates/products toward the biocatalyst (Erol and Hollmann 2021 ; Jung et al 2013 ). It was reported that NADESs can improve the mass transfer efficiency by enhancing the permeability of cell membrane, and alleviate substrate/product inhibition (Xia et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%